Implementation of A Combination Of WP and Moora Methods in Recruitment Of Casual Daily Laborers to Become Permanent Employees - Sanjaya, Bima; Irawan, Muhammad Dedi (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2025)
The Industrial Revolution 4.0 has emphasized the strategic role of information technology in supporting organizational decision-making, particularly in workforce recruitment. Within this context, PTPN IV, a leading company in the plantation sector, continues to encounter challenges in promoting Casual Daily Laborers (BHL) to permanent employees through an objective and transparent selection process. To address this issue, this study introduces a decision support system (DSS) that integrates the Weighted Product (WP) method with Multi-Objective Optimization by Ratio Analysis (MOORA). The WP method is applied to calculate preference values based on weighted criteria, while MOORA facilitates multi-criteria optimization, thereby strengthening the accuracy of the ranking process. Empirical findings indicate that the combined approach significantly enhances decision-making effectiveness, producing more consistent and fair outcomes compared to conventional methods. The practical implication of this research lies in providing PTPN IV with a reliable tool to improve efficiency, ensure fairness, and strengthen accountability in employee promotion decisions, which ultimately contributes to organizational performance and competitiveness.